Study of thyroid volume by ultrasonography in clinically euthyroid patients (Journal of Institute of Medicine Nepal, 2011)
Introduction: The purpose of this study was to establish reference ranges of total thyroid volume among clinically euthyroid Nepalese population using Ultrasonography and correlate this volume with age, sex, individual’s built and geographic location. Methods: This was a prospective cross sectional study involving 485 clinically euthyroid individuals. B - mode Ultrasonography was used to measure the total thyroid volume by combining the volume of both the lobes obtained by using formula for prolate ellipsoid. Age specific reference values for thyroid volume were obtained and Pearson correlation test was used to see the relationship with various factors. Results: Among 485 individuals between 1 to 83 years of age, 221(45.57%) were males and 264(54.43%) were females. Maximum [354 individuals (72.99%)] were from hilly region and minimum [16 individual (3.30%)] were from Himalayan region. Mean thyroid volume was 6.629 ± 2.5025 ml. In general, thyroid volume was found to be more in older individuals than in young age group. There was no significant difference of thyroid volume between males and females. Thyroid volume best correlated with body surface area (r=0.444, p